2014
DOI: 10.1063/1.4904724
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin as a new humidity sensing material: Characterization and limitations

Abstract: The goal of this work is to assert the utility of collagen and its denatured counterpart gelatin as cost-effective alternatives to existing sensing layers comprised of polymers. Rather than producing a material that will need to be discarded or recycled, collagen, as a by-product of the meat and leather industry, could be repurposed. This work examines the feasibility of using collagen as a sensing layer. Planar electrodes were patterned with lift-off process to work with the natural characteristics of gelatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Dielectric polymers exhibit gas-sensing mechanisms such as dispersion, polarizability, dipolarity, basicity, acidity, and hydrogen-bonding interactions . In single-output sensors, measurements are performed with capacitance readout , unless these polymers are formulated with conducting nanoparticles to measure the change in sensor conductivity . Such sensors have known insufficient selectivity; thus, they have been assembled into classic sensor arrays. , Several reviews analyze performance of dielectric polymers in gas sensing. , …”
Section: Multivariable Nonresonant and Resonant Impedance Sensorsmentioning
confidence: 99%
“…Dielectric polymers exhibit gas-sensing mechanisms such as dispersion, polarizability, dipolarity, basicity, acidity, and hydrogen-bonding interactions . In single-output sensors, measurements are performed with capacitance readout , unless these polymers are formulated with conducting nanoparticles to measure the change in sensor conductivity . Such sensors have known insufficient selectivity; thus, they have been assembled into classic sensor arrays. , Several reviews analyze performance of dielectric polymers in gas sensing. , …”
Section: Multivariable Nonresonant and Resonant Impedance Sensorsmentioning
confidence: 99%
“…When a linear fit is applied for this lower humidity range, the slope of the fit can be considered as the sensor's sensitivity. For the sensor coated with a PDMAA monolayer a sensitivity of around 10 pF/%RH in this humidity range is obtained, which is at least 20 times higher than other polymer coated sensors with a comparable setup reported in the literature [10,13,[22][23][24][25].…”
Section: Dew-point Measurementsmentioning
confidence: 77%
“…At a higher humidity level, capacitance density across the MIM (ITO/HfO 2 /gelatin/Au) structure increases due to the higher electrical permittivity of water in comparison to gelatin and contributes to higher charge accumulation in the channel. 56 From the results, it can be observed that the current in gelatin device reaches to saturation very sharply just after exposure to humidity; similarly, during the desorption process it returns to the initial stage in considerably low time interval, which makes it suitable for highly sensitive humidity sensors. To investigate the practical utility of the device, a continuous breath rate monitoring was demonstrated with help of changes in the humidity levels of breath during exhaling and inhaling.…”
Section: Resultsmentioning
confidence: 99%